Synthesis and Characterization of a Magnetic Molecular Imprinted Polymer for Tetracycline Quantification in Food Samples - Zeb, Shakeel [UNESP]; Wong, Ademar [UNESP]; Khan, Sabir [UNESP]; Hussain, Sajjad; Sotomayor, Maria D. P. T. [UNESP] (Wiley, 2024)
In the present work, we synthesized and tested a magnetic molecularly imprinted polymer (mag-MIP) sensor for the detection of tetracycline in food samples. High-performance liquid chromatography (HPLC) and spectrofluorometry were employed for tetracycline determination. The mag-MIP was polymerized on the surface of Fe3O4@SiO2 magnetic nanoparticles using the following substances: 4 mmol of methacrylic acid as the functional monomer, 20 mmol of ethylene glycol dimethacrylate (EGDMA) as the cross-linking agent, 82.5 mg of benzoyl peroxide as the radical initiator, and 30 ml of acetonitrile as the solvent. The physicochemical characteristics of the proposed mag-MIP, including adsorption capabilities and selectivity, were studied and compared with those of a magnetic non-molecularly imprinted polymer (mag-NIP). The analytical curve was constructed in the range of 1.0×10−5–8.0×10−5 mol L−1, LOD: 3.3×10−6, LOQ: 1.1×10−5 mol L−1. The results obtained from the adsorption analysis showed that the highest adsorption capacity of the mag-MIP at equilibrium was 8.247 mg g−1 and that the tetracycline adsorption process followed the Langmuir adsorption isotherm model and pseudo-second-order reaction kinetics. The proposed mag-MIP also exhibited good results when subjected to fluorescence analysis; an increase in tetracycline concentration resulted in an increase in the adsorption capacity, and this led to the effective removal of tetracycline with the reduction of fluorescence intensity. The applicability of the proposed mag-MIP was evaluated in honey, cow milk, and egg samples through recovery tests conducted using samples containing spiked tetracycline concentration at two different concentration levels (1.7×10−5 and 2.5×10−5 mol L−1), where we obtained recovery percentages in the range of 73.2–87.2 % (HPLC) and 90.5–103.7 % (spectrofluorometry).
Keywords: and Spectro-fluorometer; Food samples; HPLC; Magnetic nanoparticles/MIP; Tetracycline antibiotics